Geometric construction of all possible H-bonded associated nucleic base pairs - Glushenkov, A.N.; Hovorun, D.M. (Reports of the National Academy of Sciences of Ukraine, 2014)
The original automated structural hypothesis creation technique for all possible pairs of hydrogen bond stabilized nucleic bases is proposed and has been tested on 1-methylcytosine on the B3LYP/6-311++G(d,p) theory level in vacuum.